Hilirisasi Produk Eco-enzyme Sebagai Upaya Mandiri Ekonomi di Masyarakat RW 11 Pamulang Timur Tangerang Selatan - Titta Novianti; Seprianto; Rini Hidayati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Retired people experience reduced income and boredom due to reduced daily activities. This was felt by retirees in RW 11 Pamulang Timur, Tangerang South. High levels of community activity at home also impact the increase in waste in the home environment. Efforts to overcome these two problems include implementing productive activities aimed at increasing household economic income and overcoming the problem of waste in the home environment. It is hoped that community service through training on ecological enzyme production from leftover vegetables or fruits can solve the waste problem and create products with high economic value. Through a 3-month fermentation process with the addition of brown sugar, an ecological enzyme liquid is created that serves as a floor cleaner, dishwashing liquid, disinfectant, bio-fertilizer as well as many other uses. Another benefit is that it contains a variety of enzymes obtained from fermentation. of lactic bacteria. The community received traditional training materials for one day, then was supported in the eco-enzyme production process for 3 months until the product was ready for harvest. The community is also trained in product marketing strategies using online media, advertising strategies, calculating costs, and selling prices, and writing simple financial reports. Production will begin in July 2023 and be ready for harvest in September 2023. Each resident produces a minimum of 1.5 liters to 5 liters of ecological enzyme solution. The resulting product is packaged in used bottles ready for the market. Some are packaged as ready-to-use products, such as hand sanitizer, shampoo, dishwashing liquid, and others. It is hoped that the proceeds from the sale of ecological enzymes can be used as a product to improve the economy at the household level with high efficiency.